2011
DOI: 10.3109/02688697.2011.631617
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of symptomatic blood blister-like aneurysm of the internal carotid artery: clinical experience and management outcome

Abstract: BBAs of the supraclinoid ICA have special neuroradiological and clinicopathological characteristics. Direct clipping or endovascular coil embolization along may not be sufficient and sometimes have undesirable results. ICA trapping or ligation including the lesion segment can be considered an alternative choice if the balloon occlusion test (BOT) is successful. However, if the patient does not tolerate the BOT, EC-IC bypass surgery with ICA ligation or trapping is another option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…11 Endovascular surgery has achieved favorable outcomes in a small number of select patients. [33][34][35][36] Although intraoperative bleeding and the resultant mortality rate are extremely high in the ultra-early phase, delayed surgery achieved a 72% favorable outcome as per data from a nationwide survey. 10 Therefore, the timing of surgery may play a major role in improving the outcomes of treatment for BBAs.…”
Section: Discussionmentioning
confidence: 91%
“…11 Endovascular surgery has achieved favorable outcomes in a small number of select patients. [33][34][35][36] Although intraoperative bleeding and the resultant mortality rate are extremely high in the ultra-early phase, delayed surgery achieved a 72% favorable outcome as per data from a nationwide survey. 10 Therefore, the timing of surgery may play a major role in improving the outcomes of treatment for BBAs.…”
Section: Discussionmentioning
confidence: 91%
“…Eighteen studies evaluated endovascular therapy only, 14 evaluated surgery only, and 4 included both endovascular and surgical interventions. 3,35,39,52 For our analysis, 22 and 18 papers were examined and analyzed for endovascular and surgical approaches, respectively.…”
Section: Study Characteristics and Designsmentioning
confidence: 99%
“…There are 2 approaches to treat BBAs, such as endovascular or direct surgery (Table 2). 7, 18, 22, 35 The number of reports using the endovascular method have been increasing because of the recent improvement of medical equipment such as a flow diverter 11, 15, 16, 17, 19, 20, 21, 36, 37, 38, 39, 40, 41, 42, 43. Previous studies comparing the 2 approaches found higher risk in the direct surgeries including accidental IC occlusions, albeit higher recurrence rate and more frequent reoperation in the endovascular treatment 18, 22, 37, 44, 45, 46.…”
Section: Discussionmentioning
confidence: 99%